La justice « témoin de soi » : l’affaire d’Outreau dans l’œil de Montaigne - François Roussel (Droit et Cultures, 2008)
The so-called Outreau case confirms the risks of dire injustice connected with preliminary investigation in France. The same goes for the practice of remanding in custody which has, for several years, kept in jail accused subsequently proved innocent. It seemed insightful here to compare some elements of this case to the analysis developed by Montaigne in his Essays regarding forms of institutional justice. Whatever the risk of sounding anachronistic, one can indeed establish startling parallels showing the persistence of an “inquisitorial culture” characterised by the presumption of guilt and the search for a confession at all costs, whatever the price to pay in terms of truth.